The Review and Analysis of the Book: "Seasons of the Transfiguration and Al-Tarib" from Experience to Translation - Reza Nazemian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The critique of the book can be considered as an extension of the writer's efforts in providing research results. Critique is the essence of the research, and this article seeks to review the book "The Seasons of the Transfiguration and Al-Tarib", written by and Egyptian writer and interpreter, Mohammed al-Batal. The book consists of eight chapters that deal with various subjects in the field of translation from Arabic to English and vice versa, and although all of these chapters, are the subject of an article, they are scattered.  They are also dedicated to specialty in translation. The area where the author pays more attention to is the field of terminology, which is a large part of the book, and even a chapter of the book forms a small culture of press terminology. Considering that books on translation theory have a relatively long history and even a few books have been published in Arabic, the book "The Fosoolfi al-tarjomah va al- tarib" was expected from Mohammad al-Batal which was published in 2007 to deepen the field of translational studies, but a glance at the book's list of sources suggests that the author has an extensive research effort. He has not done much about translation technology and has written more practical experiences.